Tinjauan Yuridis terhadap Hukuman Pidana Pelaku Kelalaian Berat yang Mengakibatkan Kematian Bagi Pasien - Gede Arie Krishna Wirawan Putra; Jimmy Pello; Darius A. Kian (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Medical negligence is an act of medical personnel that causes harm to others that is carried out under compelling circumstances or violates the standards of the medical profession. According to Law No. 36 of 2014 states that health workers who commit negligence can be punished by criminal, with a maximum imprisonment of 3 years and 5 years if it causes death. The main problem in this research is whether the criminal punishment against the defendant of medical malpractice is in accordance with the defendant's actions?. This research was conducted using normative juridical method with legal material collection techniques, namely with statutory and conceptual approaches, the materials that have been collected are then analyzed and arranged systematically. The results showed that the prosecutor's indictment must meet the formal and material requirements listed in Article 143 of the Criminal Procedure Code, in legal cases whether the indictment is in accordance with applicable laws and regulations or not is only determined by the judicial process, it is the court that assesses the facts or evidence in court so that it becomes valid. The panel of judges, by assessing and considering the legal facts, considered that the charges of the public prosecutor were too severe and needed to be reduced so that the purpose of the sentence could be more appropriate and provide maximum benefit.